PTU-081 Are we Exposing Patients with a Mildly Elevated Faecal Calprotectin to Unnecessary Investigations?. (4th June 2013) - Seenan, J P; Thomson, F; Rankin, K; Smith, K; Gaya, D R
Abstract : Introduction: Faecal calprotectin (FC) is increasingly used as a non-invasive marker to differentiate irritable bowel syndrome (IBS) from inflammatory bowel disease (IBD). However, it is a non-specific marker of luminal inflammation and false positives are common. We have previously demonstrated a low yield of diagnostic colonoscopy in patients with borderline elevations of FC (50–100 µg/g). Higher FC levels (100–200 µg/g) often prompt more extensive investigation. We sought to determine the diagnostic yield of endoscopic/radiological investigation in patients presenting with new lower GI symptoms and a mildly elevated FC (100–200 µg/g). Methods: All patients with a faecal calprotectin 100–200 µg/g were identified from our biochemistry laboratory database between September 2009 and September 2011. Patients aged 16 to 50 years attending gastroenterology outpatient clinics with new lower GI symptoms were identified. Patients were excluded if they had a previous FC > 200 µg/g, were taking NSAIDs, had known IBD, positive stool cultures or any 'alarm' symptoms. Details of investigations, diagnosis and clinical outcomes were determined electronically from the NHS Greater Glasgow and Clyde Clinical Portal. Results: 163 patients (104 female) were identified who met the inclusion criteria. The mean age was 37.5 years with a mean FC of 146.6µg/g. The primary presenting complaint was diarrhoea in 100 (61.3%) and abdominal pain in 63 (38.7%). Secondary symptoms were abdominal pain (28.2%), diarrhoea (18.4%) and constipation (1.8%). A total of 390 endoscopic, radiological and histological investigations were undertaken in 152 patients with an average of 2.6 investigations per patient. 131 colonoscopies were performed with abnormalities detected in only 23 (17.6%). In patients with a macroscopically normal upper GI endoscopy and colonoscopy, the diagnostic yield of any further investigation was only 7%. The negative predictive value (NPV) of a FC 100–200 µg/g was 86.9% for any pathology and 98.1% for significant luminal pathology (IBD, advanced adenoma or colorectal carcinoma). IBD was the final diagnosis in only 3 (1.8%) of patients while 48.5% were diagnosed as having IBS. Conclusion: In adult patients under 50 years old presenting with new lower GI symptoms, the NPV of a FC between 100 and 200µg/g in excluding significant organic GI disease is high. Patients are often extensively investigated yet the overall diagnostic yield is very low and the majority of these patients have functional disease. We suggest that the manufacturer's FC cut off of 50 µg/g of stool is too low for utilisation in clinical practise and often results in unnecessary, invasive investigations. Disclosure of Interest: None Declared